ANALISIS STRUKTUR BATIN DAN STRUKTUR FISIK PADA PUISI “IBU” KARYA D. ZAWAWI IMRON - Dendy Ginanjar; Fajar Kurnia; Nofianty Nofianty (IKIP Siliwangi, 2018)
This study aims to (1) analyze the inner structure and physical structure of his poetry D. Zawawi Imron entitled